Ultra-high performance concrete and preparation method thereof
Ultra-high performance concrete is prepared by using waste incineration bottom slag and fly ash as aggregate, combined with calcium carbonate whiskers, acrylamide in situ polymerization solution and PVC fiber, which solves the low proportion of waste incineration and low comprehensive utilization rate. The problem has achieved cost reduction and mechanical performance improvement.
Patent Information
- Application Number
- CN202411473991.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-22
AI Technical Summary
In the prior art, waste incineration accounts for a low proportion of ultra-high performance concrete, and the comprehensive utilization rate is low, resulting in high production costs.
Ultimate concrete is prepared by using waste incineration bottom slag and fly ash as aggregate, combined with calcium carbonate whiskers, acrylamide in situ polymerization solution and PVC fiber, which significantly improves the application ratio of waste incineration products and the mechanical properties of concrete.
It significantly improves the utilization rate of waste incineration products, reduces the production cost of ultra-high performance concrete, and improves the mechanical properties of concrete.
Smart Images

Figure BDA0005095503270000101 
Figure BDA0005095503270000111
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of concrete, and in particular to an ultra-high performance concrete and a preparation method thereof. Background Art
[0002] Ultra-high performance concrete is a new type of cement-based composite material with excellent mechanical properties and durability. However, the amount of cement used in the preparation of ultra-high performance concrete is 2-3 times that of ordinary concrete, which makes ultra-high performance concrete have a higher cost. The chemical elements of garbage incineration waste are mainly Ca, Si, Al and Fe, belonging to the CaO-Al2O3-SiO2-Fe2O3 system, which is similar to the composition of raw materials for cement production. Therefore, in the existing technology, the use of garbage incineration waste as raw materials to prepare ultra-high performance concrete can not only effectively reduce the amount of cement used and reduce the production cost of ultra-high concrete, but also significantly improve the resource utilization efficiency of garbage incineration waste.
[0003] Waste from garbage incineration generally includes garbage incineration bottom ash and garbage incineration fly ash. The prior art has disclosed technical solutions for preparing ultra-high performance concrete using garbage incineration fly ash and garbage incineration bottom ash, such as a green and environmentally friendly ultra-high performance concrete material and a preparation method thereof disclosed in publication number CN113443872A. This technical solution fixes heavy metals in fly ash in concrete through the hydration of cement and fly ash, and reduces the problem of excessive water absorption of fly ash through a water reducer, so that garbage fly ash can replace part of the cement to reduce the amount of cement used without significantly changing the performance of the ultra-high performance concrete. Another example is an ultra-high performance concrete and a preparation method thereof disclosed in publication number CN116903330A. In this technical scheme, fly ash and zeolite are used to make calcined zeolite, silica ash and polycarbonate activated silica are used to coat garbage bottom residue, and then the calcined zeolite and garbage bottom residue are used to prepare ultra-high performance concrete. Alkali-silica gel is produced by garbage incineration bottom residue and concrete to increase the internal humidity of concrete and reduce the drying shrinkage of concrete. The calcined zeolite can absorb cement hydration products and play a role in internal maintenance. At present, the proportion of garbage incineration materials in ultra-high performance concrete in the existing technology is low, and the utilization efficiency of garbage incineration bottom residue is low. Summary of the invention
[0004] In order to overcome the problem of low proportion and low comprehensive utilization rate of waste incineration materials in ultra-high performance concrete under the existing technical conditions, the present invention provides an ultra-high performance concrete and a preparation method thereof. In this scheme, waste incineration bottom slag and waste incineration fly ash are made into aggregate, calcium carbonate whiskers, acrylamide in-situ polymerization solution and PVC fibers are used to prepare ultra-high performance concrete, which significantly increases the application ratio of waste incineration products in ultra-high performance concrete, significantly reduces the cost of ultra-high performance concrete, and the concrete has excellent mechanical properties.
[0005] The specific technical scheme of the present invention is: An ultra-high performance concrete comprises, by weight, 600-850 parts of cement, 120-180 parts of fly ash, 200-250 parts of silica fume, 1000-1450 parts of aggregate, 180-225 parts of water, 7-12 parts of water reducing agent, 15-20 parts of acrylamide in-situ polymerization solution, 5-8.5 parts of PVC fiber, and 9-12.5 parts of calcium carbonate whisker.
[0006] Preferably, the aggregate is made by wrapping detoxified fly ash on waste incineration bottom ash, the detoxified fly ash is made by thermally desorbing dioxins from acid leaching residue, and the acid leaching residue is made by acid leaching fly ash and filtering the residue.
[0007] Preferably, the particle size of the waste incineration ash is 6.75 to 16 mm.
[0008] Preferably, the pH of the acid leaching treatment is 2-3.
[0009] Preferably, the calcium carbonate whiskers are made of crude brine and carbon dioxide, wherein the crude brine is made by removing heavy metals and sulfides from an acid leaching solution obtained by acid leaching fly ash and filtering the filtrate.
[0010] Preferably, the calcium carbonate whiskers are modified calcium carbonate whiskers, which are prepared by using calcium carbonate whiskers as raw materials and undergoing modification treatment with sodium hydroxide and tetraethyl orthosilicate.
[0011] Preferably, the acrylamide in-situ polymerization solution is prepared from acrylamide, ammonium persulfate and N,N'-methylenebisacrylamide as raw materials.
[0012] The present application provides an ultra-high performance concrete, in which the aggregate in the concrete raw materials is made of acid leaching filtrate of fly ash from incineration of garbage and bottom ash from incineration of garbage, and the calcium carbonate whiskers are made of acid leaching filtrate of fly ash from incineration of garbage as raw materials. The garbage incineration waste includes bottom ash from incineration of garbage and fly ash, wherein the bottom ash is a granular inert compactable material containing siliceous compounds, calcium compounds and anhydrite, and has the same volcanic ash activity and hydraulic hardness as lime and cement. Fly ash belongs to the CaO-Al2O3-SiO2-Fe2O3 system, has the activity of volcanic ash, and the particle size of fly ash is relatively fine. It can be prepared into aggregate by combining with garbage bottom slag, which can correct the low fine material content characteristic of bottom slag, thereby improving the compaction of concrete. In addition, acrylamide is added to ultra-high performance concrete, which can hydrolyze in large quantities to produce carboxyl groups in the alkaline environment of cement-based concrete, and bond with the metal ions of the hydration products to form a strong skeleton network system, changing the mechanical properties of concrete. Adding PVC fiber can reduce the porosity of concrete, organize the expansion of cracks, improve the density of concrete, and enhance durability. Whisker material refers to a one-dimensional single crystal material with a certain aspect ratio and a certain cross-sectional area. The protective film on the surface of the whisker absorbs Ca in the solution. 2+ , which delays the cement hydration to a certain extent. With the increase of curing age, the nucleation effect, filling effect and bridging crack prevention effect of the whiskers are exerted. The larger aspect ratio increases the contact area between the whiskers and the ultra-high performance concrete matrix, and the interfacial bonding between the two is stronger, resulting in more energy consumption in the whisker extraction process, thereby enhancing the mechanical properties of ultra-high concrete in many aspects.
[0013] In addition, the present invention forms a micro-meso-macro multi-scale modification system for ultra-high performance concrete through acrylamide in-situ polymerization solution, PVC fiber and calcium carbonate whisker. Due to the occurrence of acrylamide in-situ polymerization, a complete and uniform polymer network is formed in the concrete matrix; there is a bridging chemical bond between the carboxyl group generated after acrylamide hydrolysis and the hydration product; however, since the in-situ polymerization of acrylamide has an inhibitory effect on cement hydration, the strength of the concrete is reduced; however, the addition of PVA fiber and modified calcium carbonate whisker can avoid this problem and enhance the mechanical properties of the concrete; firstly, the addition of fiber can prevent the expansion of concrete cracks, and the addition of modified calcium carbonate whisker and PVA fiber can not only bridge the microcracks distributed inside the concrete and inhibit these microcracks from developing into macro cracks, but also prevent the expansion of macro cracks, at different structural levels. The properties of the concrete are enhanced; secondly, there is physical adsorption combining intermolecular forces and electrostatic forces between the modified calcium carbonate whiskers and the polymer network formed by the in-situ polymerization of acrylamide; at the same time, the carboxyl groups generated after the hydrolysis of acrylamide can bond with the calcium ions on the surface of the crystal, and there is chemical adsorption combined with chemical bonds; the above combined effects make the calcium carbonate whiskers and the polymer network formed by acrylamide tightly combined, forming a tightly combined interface of whisker-polymer-cementitious material, so that the whiskers are tightly combined with the concrete and the whisker agglomeration is further improved, so that the reinforcing effect of the calcium carbonate whiskers is fully exerted; furthermore, the in-situ polymerization of acrylamide will also produce a coating layer combining polymers and hydration products on the surface of PVA, which greatly enhances the bonding strength and bonding between the PVA fibers and the concrete matrix, so that the reinforcing effect of the fibers is also fully exerted, thereby enhancing the mechanical properties of the overall concrete.
[0014] A method for preparing the above-mentioned ultra-high performance concrete comprises the following steps: pouring cement, fly ash and silica fume into a stirring device and mixing them evenly, then adding aggregate, water and a water reducing agent and stirring again, adding calcium carbonate whiskers, PVC fibers and acrylamide in-situ polymerization solution in portions during the stirring process, and finally vacuum mixing and discharging to prepare ultra-high performance concrete.
[0015] Preferably, the method for preparing the aggregate comprises the following steps: preparing fly ash into slurry at a water-cement ratio of 2 to 2.5:1, adding a pickling agent into the slurry for acid leaching, filtering after the acid leaching to obtain an acid leaching residue, placing the acid leaching residue in a low-temperature pyrolysis desorption device for pyrolysis desorption of dioxins to prepare detoxified fly ash, preparing the detoxified fly ash into a coating slurry at a water-cement ratio of 0.4 to 0.6:1, adding waste incineration bottom ash into the coating slurry, stirring and drying to prepare aggregate, the pH of the acid leaching treatment is 2 to 3, the temperature of the pyrolysis desorption dioxin treatment is 450 to 550°C, and the time of the pyrolysis desorption dioxin treatment is 1 to 1.5 hours.
[0016] Preferably, the preparation method of the calcium carbonate whisker comprises the following steps: preparing fly ash into slurry according to a water-cement ratio of 2 to 2.5:1, adding a pickling agent into the slurry for acid leaching, filtering after the acid leaching to obtain an acid leaching filtrate, adjusting the pH of the acid leaching filtrate to 9.5 to 10 with sodium hydroxide and then filtering, adding 1.5 to 3 mmol / L sodium sulfide to the filtrate after filtering, separating and precipitating to obtain crude brine, pumping carbon dioxide into the crude brine until the solution is neutral, filtering to obtain a filter cake, adding the filter cake into a sodium hydroxide solution, stirring at a constant temperature of 40 to 45° C. for 10 to 12 hours, washing and drying to obtain calcium carbonate whiskers, mixing the calcium carbonate whiskers, 200 to 210 parts of anhydrous ethanol and 45 to 50 parts of deionized water, adding 2.5 to 3 parts of ammonia water, stirring for 1 to 2 hours, adding 30 to 35 parts of ethyl orthosilicate, stirring at 40 to 45° C. for 5 to 7 hours, washing and drying to obtain modified calcium carbonate whiskers.
[0017] The present application also provides a method for preparing the above-mentioned ultra-high performance concrete, in which fly ash from incineration is subjected to acid leaching treatment, and chloride ions harmful to concrete in fly ash from incineration can be removed after acid leaching treatment, and the acid leaching residue and acid leaching filtrate obtained after acid leaching treatment are treated separately, and the heavy metals in the acid leaching residue can be removed after thermal desorption of dioxins and detoxification, and the peak value of calcium carbonate in the detoxified fly ash increases, and calcium silicate is formed by solid-phase reaction and silicification reaction of calcium oxide and silicon dioxide under high temperature environment, the activity of the pretreated fly ash is enhanced and the particle size of the pretreated fly ash is fine, and after being made into slurry, it can be wrapped on the waste incineration bottom ash, which can fill the surface holes and cracks of the waste incineration bottom ash, make the surface of the waste incineration bottom ash smooth, form a high-strength matrix protective layer, and make the wrapped waste incineration bottom ash structure denser, The treated fly ash from incineration of garbage can undergo a volcanic ash reaction with the bottom ash from incineration of garbage, and the generated CSH crystals are connected to the surface of the bottom ash from incineration of garbage, are fully hydrated, and have good adhesion; the hydrated products of the pretreated fly ash slurry will produce numerous tiny voids and agglomerated hydrated products, which can significantly increase the water absorption rate of the aggregate after being wrapped on the surface of the bottom ash from incineration of garbage; in addition, due to the use of rapid drying in the wrapping slurry operation, the crystal structure is irregular and bubbles are generated inside the pretreated fly ash slurry. Drying makes the molecular activity more intense, and the gas produces more bubbles that can quickly move away from the bottom ash from incineration of garbage, but the slurry layer is thin, and the gas can quickly rush out of the slurry layer, so that no water film isolation is formed around the wrinkles of the bottom ash from incineration of garbage, and the cement hydrate does not produce large bubbles or even large cracks caused by the air barrier, thereby improving the mechanical properties of the concrete.
[0018] In this method, the acid leaching filtrate obtained from the acid leaching of waste incineration fly ash is used as a raw material to make calcium carbonate whiskers, and then the surface of the calcium carbonate whiskers is pretreated with sodium hydroxide to increase the number of hydroxyl groups on the whisker surface, and then the whiskers are surface modified with ethyl orthosilicate to enhance the bonding performance between the calcium carbonate whiskers and the cement-based interface. The surface of the modified calcium carbonate whiskers is relatively rough, and silicon dioxide produced by the hydrolysis of ethyl orthosilicate is attached to the surface. Silicon dioxide can participate in the hydration reaction of cement, increase the hydration products around the calcium carbonate whiskers, and improve the density of the cement matrix. When the cracks extend to the whisker surface, more energy is consumed to overcome the friction between the whiskers and the cement matrix interface, thereby improving the toughness of ultra-high performance concrete.
[0019] Compared with the prior art, this application has the following technical effects: The present invention adopts detoxified fly ash and garbage incineration bottom ash as aggregate of concrete, which can not only reasonably utilize resources and reduce the burden of environmental disposal, but also the detoxified fly ash is modified by acid leaching and thermal desorption to make the fly ash particle size smaller and more active. After forming slurry, it fills the holes and cracks on the surface of the garbage incineration bottom ash, makes the surface of the garbage incineration bottom ash smooth, forms a matrix protective layer with high strength, makes the structure denser, enhances the compressive resistance of the aggregate, and thus improves the mechanical properties of the concrete.
[0020] The calcium carbonate whisker used in the invention is prepared in the fly ash detoxification process, which achieves the effect of treating waste with waste and saves costs.
[0021] The invention adopts modified calcium carbonate whiskers, PVC fibers and acrylamide in-situ polymerization solution to modify cement-based materials. Acrylamide, as a microscopic modified substance, forms a complete and uniform polymer network and has a bonding effect with hydration products, thereby greatly improving the microstructure and performance of the cement-based materials. Silicon dioxide is attached to the surface of the modified calcium carbonate whiskers, thereby increasing the hydration products around the whiskers and, as a mesoscopic modified substance, its filling effect makes the structure of the cement-based materials more compact, while inhibiting the generation and expansion of microcracks and improving the mechanical strength and toughness of the cement-based materials. PVC fibers, as a macroscopic modified substance, can bear loads, inhibit cracks and improve the mechanical properties of the cement-based materials. There is a positive synergistic reinforcement effect among the three, thereby forming a microscopic, mesoscopic and macroscopic multi-scale synergistic modification and comprehensively improving the mechanical properties of concrete. DETAILED DESCRIPTION
[0022] The present invention will be further described below in conjunction with the embodiments.
[0023] Embodiment 1: An ultra-high performance concrete comprises, by weight, 850 parts of cement, 180 parts of fly ash, 240 parts of silica fume, 1400 parts of aggregate, 210 parts of water, 12 parts of water reducer, 20 parts of acrylamide in-situ polymerization solution, 8.5 parts of PVC fiber, and 12.5 parts of calcium carbonate whiskers; the cement is P042.5 silicate cement, the fly ash meets the physical and chemical performance requirements of Class II fly ash in GB / T1596-2017, and the silica fume meets the SF95 performance index of silica fume for mortar and concrete in GB / T27690-2023; the water reducer is a polycarboxylic acid high-performance water reducer (solid content is 20%, water reduction rate is 30%); the modified calcium carbonate whisker is 0.5 mm, the length is 20 mm, the PVC strength is 1600 MPa·S, and the acrylamide in-situ polymerization solution is prepared from acrylamide, ammonium persulfate and N,N'-methylenebisacrylamide as raw materials.
[0024] A method for preparing ultra-high performance concrete comprises the following steps: Fly ash pretreatment: The fly ash is made into fly ash slurry with a solid-liquid ratio of 1:2, and then the fly ash is acid-leached with hydrochloric acid. The acid-leaching treatment uses 31% hydrochloric acid by mass to adjust the pH of the fly ash slurry to 2. After the acid-leaching treatment, the solid-liquid separation is performed to obtain the acid-leaching residue and the acid-leaching filtrate; Aggregate preparation: the acid leaching residue is introduced into a rotary kiln, and after thermal desorption at 550°C for 2 hours, dioxin detoxification fly ash is obtained, and the dioxin detoxification fly ash is made into a coating slurry with a water-cement ratio of 0.4, and the bottom slag of the incinerated garbage (with a particle size of 6.75 to 9.5 mm) is immersed in the coating slurry for coating treatment to obtain a coating, and then the coating is placed in a drying box and dried at 105°C to obtain aggregate; Preparation of calcium carbonate whiskers: adjusting the pH of the acid leaching filtrate to 10 with sodium hydroxide, then filtering to remove heavy metal solids and collecting the filtrate, adding 3 mmol / L sodium sulfide to the filtrate and filtering to remove sulfide precipitation to obtain crude brine, pumping carbon dioxide into the crude brine until the crude brine becomes neutral, performing solid-liquid separation to obtain a filtrate and a filter cake, adding the filter cake to a sodium hydroxide solution (6 kg of sodium hydroxide and 250 kg of water), stirring at a constant temperature of 45° C. for 12 hours, washing and drying to obtain calcium carbonate whiskers; Preparation of ultra-high performance concrete: Cement, fly ash and silica fume are injected into a mixing device and mixed evenly, and then the above-mentioned aggregates, water and water reducer are added and continued to be stirred. During the stirring process, modified calcium carbonate whiskers, PVC fibers and acrylamide in-situ polymerization solution are added three times, and finally vacuum mixed for 4 minutes and then discharged to make ultra-high performance concrete.
[0025] Embodiment 2: An ultra-high performance concrete comprises, by weight, 720 parts of cement, 150 parts of fly ash, 220 parts of silica fume, 1350 parts of aggregate, 195 parts of water, 9 parts of water reducer, 18 parts of acrylamide in-situ polymerization solution, 7 parts of PVC fiber, and 10 parts of calcium carbonate whisker; the cement is P042.5 silicate cement, the fly ash meets the physical and chemical performance requirements of Class II fly ash in GB / T1596-2017, and the silica fume meets the SF95 performance index of silica fume for mortar and concrete in GB / T27690-2023; the water reducer is a polycarboxylic acid high-performance water reducer (solid content is 20%, water reduction rate is 30%); the modified calcium carbonate whisker is 0.8 mm, the length is 25 mm, the PVC strength is 1600 MPa·S, and the acrylamide in-situ polymerization solution is prepared from acrylamide, ammonium persulfate and N,N'-methylenebisacrylamide as raw materials.
[0026] A method for preparing ultra-high performance concrete comprises the following steps: Fly ash pretreatment: The fly ash is made into fly ash slurry with a solid-liquid ratio of 1:2, and solid-liquid separation is performed to obtain filter residue and filtrate; Aggregate preparation: the filter residue is introduced into a rotary kiln, and after thermal desorption at 500°C for 1.5 hours, dioxin detoxification fly ash is obtained, and the dioxin detoxification fly ash is made into a coating slurry with a water-cement ratio of 0.5, and the bottom slag of incinerated garbage (with a particle size of 9.5-12 mm) is immersed in the coating slurry for coating treatment to obtain a coating, and then the coating is placed in a drying box and dried at 105°C to obtain aggregate; Preparation of calcium carbonate whiskers: adjusting the pH of the filtrate to 10 with sodium hydroxide, then filtering to remove heavy metal solids and collecting the filtrate, adding 3 mmol / L sodium sulfide to the filtrate and filtering to remove sulfide precipitates to obtain crude brine, pumping carbon dioxide into the crude brine until the crude brine becomes neutral, performing solid-liquid separation to obtain a filtrate and a filter cake, adding the filter cake to a sodium hydroxide solution (6 kg of sodium hydroxide and 250 kg of water), stirring at a constant temperature of 45° C. for 12 hours, washing and drying to obtain calcium carbonate whiskers; Preparation of ultra-high performance concrete: Cement, fly ash and silica fume are injected into a mixing device and mixed evenly, and then the above-mentioned aggregates, water and water reducer are added and continued to be stirred. During the stirring process, modified calcium carbonate whiskers, PVC fibers and acrylamide in-situ polymerization solution are added three times, and finally vacuum mixed for 4 minutes and then discharged to make ultra-high performance concrete.
[0027] Embodiment 3: An ultra-high performance concrete comprises, by weight, 650 parts of cement, 120 parts of fly ash, 200 parts of silica fume, 1200 parts of aggregate, 185 parts of water, 8 parts of water reducer, 16 parts of acrylamide in-situ polymerization solution, 6 parts of PVC fiber, and 9 parts of calcium carbonate whisker; the cement is P042.5 silicate cement, the fly ash meets the physical and chemical performance requirements of Class II fly ash in GB / T1596-2017, and the silica fume meets the SF95 performance index of silica fume for mortar and concrete in GB / T27690-2023; the water reducer is a polycarboxylic acid high-performance water reducer (solid content is 20%, water reduction rate is 30%); the modified calcium carbonate whisker is 0.5 mm, the length is 20 mm, the PVC strength is 1600 MPa·S, and the acrylamide in-situ polymerization solution is prepared from acrylamide, ammonium persulfate and N,N'-methylenebisacrylamide as raw materials.
[0028] A method for preparing ultra-high performance concrete comprises the following steps: Fly ash pretreatment: The fly ash is made into fly ash slurry with a solid-liquid ratio of 1:2, and then the fly ash is acid-leached with hydrochloric acid. The acid-leaching treatment uses 31% hydrochloric acid by mass to adjust the pH of the fly ash slurry to 2. After the acid-leaching treatment, the solid-liquid separation is performed to obtain the acid-leaching residue and the acid-leaching filtrate; Aggregate preparation: the acid leaching residue is introduced into a rotary kiln, and after thermal desorption at 550°C for 2 hours, dioxin detoxification fly ash is obtained, and the dioxin detoxification fly ash is made into a coating slurry with a water-cement ratio of 0.4, and the bottom slag of the incinerated garbage (with a particle size of 6.75 to 9.5 mm) is immersed in the coating slurry for coating treatment to obtain a coating, and then the coating is placed in a drying box and dried at 105°C to obtain aggregate; Preparation of calcium carbonate whiskers: adjusting the pH of the acid leaching filtrate to 10 with sodium hydroxide, then filtering to remove heavy metal solids and collecting the filtrate, adding 3 mmol / L sodium sulfide to the filtrate and filtering to remove sulfide precipitation to obtain crude brine, pumping carbon dioxide into the crude brine until the crude brine becomes neutral, performing solid-liquid separation to obtain a filtrate and a filter cake, adding the filter cake to a sodium hydroxide solution (6 kg of sodium hydroxide and 250 kg of water), stirring at a constant temperature of 45° C. for 12 hours, washing and drying to obtain calcium carbonate whiskers; Preparation of ultra-high performance concrete: Cement, fly ash and silica fume are injected into a mixing device and mixed evenly, and then the above-mentioned aggregates, water and water reducer are added and continued to be stirred. During the stirring process, modified calcium carbonate whiskers, PVC fibers and acrylamide in-situ polymerization solution are added three times. Finally, the ultra-high performance concrete is produced after vacuum mixing for 6 minutes.
[0029] Embodiment 4: An ultra-high performance concrete comprises, by weight, 850 parts of cement, 180 parts of fly ash, 240 parts of silica fume, 1400 parts of aggregate, 210 parts of water, 12 parts of water reducer, 20 parts of acrylamide in-situ polymerization solution, 8.5 parts of PVC fiber, and 12.5 parts of calcium carbonate whiskers; the cement is P042.5 silicate cement, the fly ash meets the physical and chemical performance requirements of Class II fly ash in GB / T1596-2017, and the silica fume meets the SF95 performance index of silica fume for mortar and concrete in GB / T27690-2023; the water reducer is a polycarboxylic acid high-performance water reducer (solid content is 20%, water reduction rate is 30%); the modified calcium carbonate whisker is 0.5 mm, the length is 20 mm, the PVC strength is 1600 MPa·S, and the acrylamide in-situ polymerization solution is prepared from acrylamide, ammonium persulfate and N,N'-methylenebisacrylamide as raw materials.
[0030] A method for preparing ultra-high performance concrete comprises the following steps: Fly ash pretreatment: The fly ash is made into fly ash slurry with a solid-liquid ratio of 1:2, and then the fly ash is acid-leached with hydrochloric acid. The acid-leaching treatment uses 31% hydrochloric acid by mass to adjust the pH of the fly ash slurry to 2. After the acid-leaching treatment, the solid-liquid separation is performed to obtain the acid-leaching residue and the acid-leaching filtrate; Aggregate preparation: the acid leaching residue is introduced into a rotary kiln, and after thermal desorption at 500°C for 2 hours, dioxin detoxification fly ash is obtained, and the dioxin detoxification fly ash is made into a coating slurry with a water-cement ratio of 0.6, and the bottom slag of incinerated garbage (with a particle size of 9.5 to 12 mm) is immersed in the coating slurry for coating treatment to obtain a coating, and then the coating is naturally dried to obtain aggregate; Preparation of calcium carbonate whiskers: adjusting the pH of the acid leaching filtrate to 10 with sodium hydroxide, then filtering to remove heavy metal solids and collecting the filtrate, adding 3 mmol / L sodium sulfide to the filtrate and filtering to remove sulfide precipitation to obtain crude brine, pumping carbon dioxide into the crude brine until the crude brine becomes neutral, performing solid-liquid separation to obtain a filtrate and a filter cake, adding the filter cake to a sodium hydroxide solution (6 kg of sodium hydroxide and 250 kg of water), stirring at a constant temperature of 45° C. for 12 hours, washing and drying to obtain calcium carbonate whiskers; Preparation of ultra-high performance concrete: Cement, fly ash and silica fume are injected into a mixing device and mixed evenly, and then the above-mentioned aggregates, water and water reducer are added and continued to be stirred. During the stirring process, modified calcium carbonate whiskers, PVC fibers and acrylamide in-situ polymerization solution are added three times, and finally vacuum mixed for 4 minutes and then discharged to make ultra-high performance concrete.
[0031] Embodiment 5: An ultra-high performance concrete comprises, by weight, 850 parts of cement, 180 parts of fly ash, 240 parts of silica fume, 1400 parts of aggregate, 210 parts of water, 12 parts of water reducer, 20 parts of acrylamide in-situ polymerization solution, 8.5 parts of PVC fiber, and 12.5 parts of calcium carbonate whiskers; the cement is P042.5 silicate cement, the fly ash meets the physical and chemical performance requirements of Class II fly ash in GB / T1596-2017, and the silica fume meets the SF95 performance index of silica fume for mortar and concrete in GB / T27690-2023; the water reducer is a polycarboxylic acid high-performance water reducer (solid content is 20%, water reduction rate is 30%); the modified calcium carbonate whisker is 0.5 mm, the length is 20 mm, the PVC strength is 1600 MPa·S, and the acrylamide in-situ polymerization solution is prepared from acrylamide, ammonium persulfate and N,N'-methylenebisacrylamide as raw materials.
[0032] A method for preparing ultra-high performance concrete comprises the following steps: Fly ash pretreatment: The fly ash is made into fly ash slurry with a solid-liquid ratio of 1:2, and then the fly ash is acid-leached with hydrochloric acid. The acid-leaching treatment uses 31% hydrochloric acid by mass to adjust the pH of the fly ash slurry to 2. After the acid-leaching treatment, the solid-liquid separation is performed to obtain the acid-leaching residue and the acid-leaching filtrate; Preparation of aggregate: Manually select waste incineration slag with a particle size of 9.5 to 16 mm as aggregate; Preparation of calcium carbonate whiskers: adjusting the pH of the acid leaching filtrate to 10 with sodium hydroxide, then filtering to remove heavy metal solids and collecting the filtrate, adding 3 mmol / L sodium sulfide to the filtrate and filtering to remove sulfide precipitation to obtain crude brine, pumping carbon dioxide into the crude brine until the crude brine becomes neutral, performing solid-liquid separation to obtain a filtrate and a filter cake, adding the filter cake to a sodium hydroxide solution (6 kg of sodium hydroxide and 250 kg of water), stirring at a constant temperature of 45° C. for 12 hours, washing and drying to obtain calcium carbonate whiskers; Preparation of ultra-high performance concrete: Cement, fly ash and silica fume are injected into a mixing device and mixed evenly, and then the above-mentioned aggregates, water and water reducer are added and continued to be stirred. During the stirring process, modified calcium carbonate whiskers, PVC fibers and acrylamide in-situ polymerization solution are added three times, and finally vacuum mixed for 4 minutes and then discharged to make ultra-high performance concrete.
[0033] Embodiment 6: An ultra-high performance concrete comprises, by weight, 850 parts of cement, 180 parts of fly ash, 240 parts of silica fume, 1400 parts of aggregate, 210 parts of water, 12 parts of water reducer, 20 parts of acrylamide in-situ polymerization solution, 8.5 parts of PVC fiber, and 12.5 parts of calcium carbonate whiskers; the cement is P042.5 silicate cement, the fly ash meets the physical and chemical performance requirements of Class II fly ash in GB / T1596-2017, and the silica fume meets the SF95 performance index of silica fume for mortar and concrete in GB / T27690-2023; the water reducer is a polycarboxylic acid high-performance water reducer (solid content is 20%, water reduction rate is 30%); the modified calcium carbonate whisker is 0.5 mm, the length is 20 mm, the PVC strength is 1600 MPa·S, and the acrylamide in-situ polymerization solution is prepared from acrylamide, ammonium persulfate and N,N'-methylenebisacrylamide as raw materials.
[0034] A method for preparing ultra-high performance concrete comprises the following steps: Fly ash pretreatment: The fly ash is made into fly ash slurry with a solid-liquid ratio of 1:2, and then the fly ash is acid-leached with hydrochloric acid. The acid-leaching treatment uses 31% hydrochloric acid by mass to adjust the pH of the fly ash slurry to 2. After the acid-leaching treatment, the solid-liquid separation is performed to obtain the acid-leaching residue and the acid-leaching filtrate; Aggregate preparation: the acid leaching residue is introduced into a rotary kiln, and after thermal desorption at 550°C for 2 hours, dioxin detoxification fly ash is obtained, and the dioxin detoxification fly ash is made into a coating slurry with a water-cement ratio of 0.4, and the bottom slag of the incinerated garbage (with a particle size of 6.75 to 9.5 mm) is immersed in the coating slurry for coating treatment to obtain a coating, and then the coating is placed in a drying box and dried at 105°C to obtain aggregate; Preparation of calcium carbonate whiskers: sodium hydroxide is used to adjust the pH of the acid leaching filtrate to 9.5-10, and then the heavy metal solids are removed by suction filtration and the filtrate is collected, 1.5-3 mmol / L sodium sulfide is added to the filtrate and then filtered to remove the sulfide precipitate to obtain crude brine, carbon dioxide is pumped into the crude brine until the crude brine is neutral and solid-liquid separation is performed to obtain a filtrate and a filter cake, 26 kg of the filter cake is added to a sodium hydroxide solution (6 kg of sodium hydroxide and 250 kg of water) and stirred at a constant temperature of 40-45°C for 10-12 hours, and calcium carbonate whiskers are obtained after washing and drying, and calcium carbonate whiskers are mixed, 210 kg of anhydrous ethanol and 50 kg of deionized water are added, 2.9 kg of ammonia water is added, and stirred for 1-2 hours, and then 33 kg of ethyl orthosilicate is added and stirred at 45°C for 7 hours, and then washed and dried to obtain modified calcium carbonate whiskers.
[0035] Preparation of ultra-high performance concrete: Cement, fly ash and silica fume are injected into a mixing device and mixed evenly, and then the above-mentioned aggregates, water and water reducer are added and continued to be stirred. During the stirring process, modified calcium carbonate whiskers, PVC fibers and acrylamide in-situ polymerization solution are added three times, and finally vacuum mixed for 4 minutes and then discharged to make ultra-high performance concrete.
[0036] Embodiment 7: An ultra-high performance concrete comprises, by weight, 850 parts of cement, 180 parts of fly ash, 240 parts of silica fume, 1400 parts of aggregate, 210 parts of water, 12 parts of water reducer, 20 parts of acrylamide in-situ polymerization solution, 8.5 parts of PVC fiber, and 12.5 parts of calcium carbonate whiskers; the cement is P042.5 silicate cement, the fly ash meets the physical and chemical performance requirements of Class II fly ash in GB / T1596-2017, and the silica fume meets the SF95 performance index of silica fume for mortar and concrete in GB / T27690-2023; the water reducer is a polycarboxylic acid high-performance water reducer (solid content is 20%, water reduction rate is 30%); the modified calcium carbonate whisker is 0.5 mm, the length is 20 mm, the PVC strength is 1600 MPa·S, and the acrylamide in-situ polymerization solution is prepared from acrylamide, ammonium persulfate and N,N'-methylenebisacrylamide as raw materials.
[0037] A method for preparing ultra-high performance concrete comprises the following steps: Fly ash pretreatment: The fly ash is made into fly ash slurry with a solid-liquid ratio of 1:2, and then the fly ash is acid-leached with hydrochloric acid. The acid-leaching treatment uses 31% hydrochloric acid by mass to adjust the pH of the fly ash slurry to 2. After the acid-leaching treatment, the solid-liquid separation is performed to obtain the acid-leaching residue and the acid-leaching filtrate; Aggregate preparation: the acid leaching residue is introduced into a rotary kiln, and after thermal desorption at 550°C for 2 hours, dioxin detoxification fly ash is obtained, and the dioxin detoxification fly ash is made into a coating slurry with a water-cement ratio of 0.4, and the bottom slag of the incinerated garbage (with a particle size of 6.75 to 9.5 mm) is immersed in the coating slurry for coating treatment to obtain a coating, and then the coating is placed in a drying box and dried at 105°C to obtain aggregate; Preparation of calcium carbonate whiskers: sodium hydroxide is used to adjust the pH of the acid leaching filtrate to 9.5-10, then the filtrate is allowed to stand and filtered to remove heavy metal solids and the filtrate is collected, 1.5-3 mmol / L sodium sulfide is added to the filtrate and filtered to remove sulfide precipitates to obtain crude brine, carbon dioxide is pumped into the crude brine until the crude brine becomes neutral and solid-liquid separation is performed to obtain a filtrate and a filter cake, 30 kg of the filter cake, 210 kg of anhydrous ethanol and 50 kg of deionized water are mixed, 2.9 kg of ammonia water is added and stirred for 1-2 hours, and then 33 kg of ethyl orthosilicate is added and stirred at 45°C for 7 hours, washed and dried to obtain modified calcium carbonate whiskers.
[0038] Preparation of ultra-high performance concrete: Cement, fly ash and silica fume are injected into a mixing device and mixed evenly, and then the above-mentioned aggregates, water and water reducer are added and continued to be stirred. During the stirring process, modified calcium carbonate whiskers, PVC fibers and acrylamide in-situ polymerization solution are added three times, and finally vacuum mixed for 4 minutes and then discharged to make ultra-high performance concrete.
[0039] Comparative Example 1: Compared with Example 1, in Comparative Example 1, no calcium carbonate whiskers and acrylamide in-situ polymerization solution were added.
[0040] Comparative Example 2: Compared with Example 1, in Comparative Example 2, no PVC fiber and acrylamide in-situ polymerization solution were added.
[0041] Comparative Example 3: Compared with Example 1, in Comparative Example 3, no calcium carbonate whiskers and PVC fibers were added.
[0042] Comparative Example 4: Compared with Example 1, vacuum mixing and discharging was not adopted in Comparative Example 4.
[0043] Test example: The performance of the ultra-high performance concrete obtained in Examples 1 to 7 and Comparative Examples 1 to 4 was tested, and the test items included the following indicators: Flowability: Referring to GB / T50080-2016, the ultra-high performance concrete paste is evenly loaded into a micro-slump cone in layers. The diameter of the lower opening of the slump cone is 100mm, the diameter of the upper opening is 50mm, and the height is 150mm. Use a flat shovel to smooth the upper opening of the slump cone and lift the slump cone vertically upward. After the ultra-high performance concrete paste stops flowing, measure the two diameters of the paste in the vertical direction, and then take the average of the two diameters as the fluidity parameter of the paste. Flexural strength: Flexural strength test was conducted in accordance with GB / T17671-1999 Cement mortar strength test method (ISO method). The test steps include: the test block for flexural strength test is a 40mm×40mm×160mm prism, and the loading rate of the instrument is 0.05kN / s. Data exceeding the average value ±10% in the test results were eliminated, and the average value was taken as the flexural strength of the test block; Compressive strength: The compressive strength of the side of the half prism is tested, and the loading rate of the instrument is 2.4kN / s. The data exceeding ±10% of the average value in the test results are eliminated, and the average value is taken as the compressive strength of the test block; The test results are shown in Table 1; Table 1 Ultra-high performance concrete performance test results As shown in Table 1, in Example 1 and Example 2, Example 2 uses the aggregate prepared in Preparation Example 2, and the fly ash has not been subjected to acid leaching and high-temperature detoxification treatment, and contains a large amount of heavy metals, which invade the particle layers during the CSH hydration and deposition process, and have low activity, resulting in a decrease in both compressive strength and flexural strength.
[0044] In both Example 1 and Example 3, detoxified fly ash and waste incineration bottom ash are mixed to prepare aggregate. The detoxified fly ash slurry can fill the holes of the waste incineration bottom ash, making the prepared aggregate denser, and greatly improving the strength of the aggregate through the filling and wrapping effects.
[0045] The aggregate in Example 4 is made by natural drying. The natural drying process is not as intense as the rapid drying process, and the gas cannot rush out of the slurry layer quickly, resulting in the formation of a water film around the wrinkles of the garbage incineration bottom ash, large bubbles in the cement hydrate and even large cracks in the air barrier, resulting in a decrease in compressive strength and flexural resistance.
[0046] The aggregate in Example 5 was not wrapped with detoxified fly ash slurry, but directly used the bottom ash from incineration of garbage as aggregate. Due to the rough surface and many holes of the bottom ash from incineration of garbage, the loose crystal joints, large crystal gaps and porous microscopic characteristics, the mechanical properties of the ultra-high performance concrete produced are poor.
[0047] Both Example 6 and Example 7 use modified calcium carbonate whiskers, and the compressive strength and flexural strength are increased. This is because silica is attached to the surface of the modified calcium carbonate whiskers, and silica participates in the hydration reaction, which increases the hydration products around the calcium carbonate whiskers and improves the density of the cement matrix. When subjected to external force, more energy is required to overcome the friction between the interfaces, thereby improving the mechanical properties. In addition, compared with Example 6, when modifying the calcium carbonate whiskers, Example 7 does not add sodium hydroxide to pretreat the whisker surface. Compared with Example 6, Example 7 has lower compressive strength and flexural strength, indicating that surface pretreatment with sodium hydroxide can increase the number of hydroxyl groups on the whisker surface and enhance the bonding performance between interfaces.
[0048] Compared with Example 1, no calcium carbonate whisker and acrylamide were added in Comparative Example 1, no PVC fiber and acrylamide were added in Comparative Example 2, and no calcium carbonate whisker and PVC fiber were added in Comparative Example 3. The compressive strength of Comparative Examples 1-3 was poor, and the flexural strength was average. The above results show that the addition of the three affects each other. The in-situ polymerization of acrylamide changes the surface structure of calcium carbonate whisker and PVA fiber, improves the bonding strength of whisker, fiber and cement matrix, and the reinforcing effect of whisker and fiber is fully exerted. Acrylamide in-situ polymerization, calcium carbonate whisker, and PVA fiber play a role from different scales, and there is a positive mutual synergistic effect at the same time, forming a multi-scale composite modification mechanism of micro-meso-macro, which greatly improves the comprehensive mechanical properties of the material.
[0049] The ultra-high performance concrete provided by the present invention increases the application ratio of waste incineration products in concrete, significantly improves the utilization rate of waste incineration products, and significantly reduces the cost of ultra-high performance concrete. The ultra-high performance concrete prepared by the present invention has excellent mechanical properties and meets the use standards of ultra-high performance concrete.
[0050] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. An ultra-high performance concrete, characterized in that: Calculated by weight, it includes: 600-850 parts of cement, 120-180 parts of fly ash, 200-250 parts of silica fume, 1000-1450 parts of aggregate, 180-225 parts of water, 7-12 parts of water reducer, 15-20 parts of acrylamide in-situ polymerization solution, 5-8.5 parts of PVC fiber, and 9-12.5 parts of calcium carbonate whiskers.
2. The ultra-high performance concrete according to claim 1, characterized in that: The aggregate is made by wrapping detoxified fly ash on waste incineration bottom ash, the detoxified fly ash is made by thermally desorbing dioxins from acid leaching residue, and the acid leaching residue is made by acid leaching fly ash and filtering to obtain the residue.
3. The ultra-high performance concrete according to claim 2, characterized in that: The particle size of the waste incineration bottom ash is 6.75-16 mm.
4. The ultra-high performance concrete according to claim 2, characterized in that: The pH of the acid leaching treatment is 2-3.
5. The ultra-high performance concrete according to claim 1, characterized in that: The calcium carbonate whiskers are made of crude brine and carbon dioxide. The crude brine is made by removing heavy metals and sulfides from fly ash by acid leaching and filtering the filtrate to obtain an acid leaching solution as a raw material.
6. The ultra-high performance concrete according to claim 5, characterized in that: The calcium carbonate whisker is a modified calcium carbonate whisker, which is prepared by using calcium carbonate whisker as a raw material and undergoing modification treatment with sodium hydroxide and tetraethyl orthosilicate.
7. The ultra-high performance concrete according to claim 1, characterized in that: The acrylamide in-situ polymerization solution is prepared from acrylamide, ammonium persulfate and N,N'-methylenebisacrylamide as raw materials.
8. A method for preparing ultra-high performance concrete according to any one of claims 1 to 7, characterized in that: The following steps are involved: Pour cement, fly ash and silica fume into a mixing device and mix evenly, then add aggregate, water and water reducer and mix again, add calcium carbonate whiskers, PVC fibers and acrylamide in-situ polymerization solution in portions during the mixing process, and finally vacuum mix and discharge to prepare ultra-high performance concrete.
9. The preparation method according to claim 8, characterized in that: The preparation method of the aggregate comprises the following steps: preparing fly ash into slurry at a water-cement ratio of 2-2.5:1, adding a pickling agent into the slurry for acid leaching, filtering after the acid leaching to obtain an acid leaching residue, placing the acid leaching residue in a low-temperature pyrolysis desorption device for pyrolysis desorption of dioxins to prepare detoxified fly ash, preparing the detoxified fly ash into a coating slurry at a water-cement ratio of 0.4-0.6:1, adding waste incineration bottom ash into the coating slurry, stirring and drying to support aggregate, wherein the pH of the acid leaching treatment is 2-3, the temperature of the pyrolysis desorption dioxins treatment is 450-550°C, and the time of the pyrolysis desorption dioxins treatment is 1-1.5 h.
10. The preparation method according to claim 8, characterized in that: The preparation method of the calcium carbonate whisker comprises the following steps: preparing fly ash into slurry according to a water-cement ratio of 2-2.5:1, adding a pickling agent into the slurry for acid leaching, filtering to obtain an acid leaching filtrate after the acid leaching, adjusting the pH of the acid leaching filtrate to 9.5-10 with sodium hydroxide and then filtering, adding 1.5-3 mmol / L sodium sulfide into the filtrate after filtering, separating and precipitating to obtain a crude brine, pumping carbon dioxide into the crude brine until the solution is neutral, filtering to obtain a filter cake, adding the filter cake into a sodium hydroxide solution, stirring at a constant temperature of 40-45°C for 10-12 hours, washing and drying to obtain calcium carbonate whiskers, mixing the calcium carbonate whiskers, 200-210 parts of anhydrous ethanol and 45-50 parts of deionized water, adding 2.5-3 parts of ammonia water, stirring for 1-2 hours, adding 30-35 parts of ethyl orthosilicate, stirring at 40-45°C for 5-7 hours, washing and drying to obtain modified calcium carbonate whiskers.
Citation Information
Patent Citations
Environment-friendly ultra-high performance concrete material and preparation method thereof
CN113443872A
Ultra-high performance concrete and preparation method thereof
CN116903330A
Potassium titanate whisker reinforced ultra-high performance recycled concrete and preparation method thereof
CN117819926A
Corrosion resistant mortar composition
JP2017132667A
Method for clean and low-carbon in-situ disposal of waste incineration fly ash
US20240149207A1